Secure publish/subscribe‐based certificate status validations in mobile ad hoc networks. Issue 6 (24th August 2014) - Masdari, Mohammad; Jabbehdari, Sam; Bagherzadeh, Jamshid
Abstract Freshness of certificate status information is very important in validating public key certificates. However, existing certificate validation schemes suffer from high inconsistency, which makes network vulnerable to various security attacks. In this paper, we propose a new publish/subscribe‐based certificate validation scheme that provides fresh certificate status information in the mobile ad hoc networks. This scheme increases the security of public key infrastructure‐based security systems and improves the scalability of certificate validation systems. Also, according to the simulation results, our solution effectively decreases the processing overheads on responder nodes and reduces the messaging overhead of certificate status validations in mobile ad hoc networks. Copyright © 2014 John Wiley & Sons, Ltd.